Temporal effects of low-dose ACE inhibition on endothelial function in Type 1 diabetic patients - (:unkn) unknown (SPRINGER, 2007)
Aim: Increased asymmetrical dimethylarginine (ADMA) is known to disturb endothelial function. ACE inhibitors decrease plasma ADMA levels in diseases associated with endothelial dysfunction. The effects of ACE inhibition on endothelial function and plasma ADMA levels in Type 1 diabetic patients was evaluated in the study. Methods: Thirty Type 1 diabetic patients [29 +/- 6 yr; females (F)/males (M): 18/12] and 29 controls (30 +/- 6 yr; F/M: 16/13) were recruited. Flow-mediated dilatation (FMD), plasma ADMA and thiobarbituric acid reactive substances (TBARs) were determined at baseline, on day 15 and 90 of 0.5 mg qd trandolapril therapy. Results: Compared to controls, baseline FMD levels were lower (4.7 +/- 2.0% vs 11.2 +/- 3.9%) (p<0.001), plasma ADMA (271.1 +/- 48.1 nmol/l vs 237.5 +/- 25.1 nmol/l) (p<0.05) and TBARs levels [4517.1 +/- 2366.9 nmol/malondialdehyde (MDA) vs 1775.9 +/- 598.7 nmol/MDA] (p<0.001) were higher in diabetic patients. On day 90 of trandolapril treatment, FMD (8.6 +/- 4.1 %) (p<0.01) increased, ADMA levels (229.6 +/- 42.9 nmol/l) (p<0.001) decreased and TBARs levels (1531.8 +/- 1036.0 nmol/MDA) (p<0.001) decreased significantly. FMD was negatively correlated with plasma ADMA (r=-0.228, p<0.01), and TBARs levels (r=-0.244, p=0.02), whereas ADMA and TBARs levels were correlated positively (r=0.399, p<0.0001). Conclusions: In conclusion, endothelial dysfunction is associated with elevated plasma ADMA levels in Type 1 diabetic patients. Low-dose ACE inhibition improves endothelial dysfunction and reduces ADMA levels. The antioxidant action of ACE inhibitors may play role in this process.
Keywords: Type 1 diabetes mellitus; endothelial dysfunction; asymmetrical dimethylarginine; ACE inhibition; oxidative stress; CONVERTING ENZYME-INHIBITION; NITRIC-OXIDE SYNTHESIS; PLASMA ASYMMETRIC DIMETHYLARGININE; MYOCARDIAL-INFARCTION; SYNTHASE INHIBITOR; BRACHIAL-ARTERY; RISK-FACTOR; MELLITUS; DYSFUNCTION; MICROALBUMINURIA